2004
DOI: 10.1063/1.1826215
|View full text |Cite|
|
Sign up to set email alerts
|

Resonant tunneling transients and decay for a one-dimensional double barrier potential

Abstract: Erratum: "Resonant tunneling transients and decay for a one-dimensional double barrier structure" [J. Appl. Phys.97, 013705 (2005)] J. Appl. Phys. 99, 089901 (2006); 10.1063/1.2175355 Observation of resonant tunneling through a quantized state in InP quantum dots in a double-barrier heterostructure Appl.Motivated by recent experimental work on quantum dots subjected to voltage pulses we consider a simple model to study the transition between off-resonance and on-resonance scattering states with the same incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 37 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…It is precisely in this regime of very extended states where the approaches dealing with the time-evolution of cutoff plane waves (quantum shutter model) using resonance state expansions have proven to be useful tools to explore the dynamics in resonant structures [25]. These approaches have allowed to study the charge buildup time in double barrier structures [26][27][28][29], where it has been found that the electronic buildup obeys a capacitor charge-law characterized by a time constant of two lifetimes [27,28], and also the time scale for the fastest tunnelling response in resonant devices [30]. Gaussian wave packets and cutoff plane waves have been two different mutually exclusive dynamical approaches.…”
Section: Introductionmentioning
confidence: 99%
“…It is precisely in this regime of very extended states where the approaches dealing with the time-evolution of cutoff plane waves (quantum shutter model) using resonance state expansions have proven to be useful tools to explore the dynamics in resonant structures [25]. These approaches have allowed to study the charge buildup time in double barrier structures [26][27][28][29], where it has been found that the electronic buildup obeys a capacitor charge-law characterized by a time constant of two lifetimes [27,28], and also the time scale for the fastest tunnelling response in resonant devices [30]. Gaussian wave packets and cutoff plane waves have been two different mutually exclusive dynamical approaches.…”
Section: Introductionmentioning
confidence: 99%
“…These temporal oscillations are a pure quantum phenomenon, and similar oscillations arise at the moment of closing and opening gates in nanoscopic circuits [3]. With adequate potentials added to the model, it has been used to study transient dynamics of tunneling matter waves [4]- [7], and the transient responses to abrupt changes of the interaction potential in semiconductor structures and quantum dots [8] [9]. For a review on the subject see [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the evolution of an individual plane wave can be viewed [5] as the response of the free solution under the instantaneous onset of the potential barrier at t = 0, nowadays an experimentally feasible manipulation [6].…”
Section: Introductionmentioning
confidence: 99%